The Effect Of Mental Health Promotion On Anxiety For National Resilience Adolescent Mental Health At Smp Islam YPS Jakarta - Rindang Wahjuningtijas (Journal Of Social Science (JoSS), 2024)
Adolescents who experience mental illness often show signs such as feeling worthless, useless, unloved and unloved. These negative feelings can drive them to take extreme measures such as suicide. Therefore, promotion and education on the importance of mental health is needed for adolescents aged 12 to 17 years. This education aims to provide an understanding of what mental health is, the symptoms of mental disorders, their causes, and how to avoid them. Mental health promotion is important to prevent more serious health problems and help adolescents live their daily lives better. This research uses qualitative methods to provide an in-depth and subjective explanation of the importance of mental health promotion as a pillar of national resilience.